Capitalism, socialism and technology : a comparative study of Cuba and Jamaica - Edquist, Charles (Zed Books LondonGB, 1985)
Describes structure and actors in sugar the sector under socio-economic systems in Cuba and Jamaica. Compares technical change in sugar cane harvesting in the two countries from 1950 to the early 1980's. Examines choice of technique in sugar cane harvesting under capitalism in both countries in the early 1950's and under socialism and capitalism in Cuba and Jamaica respectively in the early 1980's. Discusses the consequences of those choices.